A (in)acessibilidade digital dos portais dos tribunais de justiça comum estaduais para pessoas com deficiência visual - Kontze, Karine Brondani (2018)
In a historical perspective, people with visual impairment are in an undeniable situation of social exclusion. In this way, it is imperative to implement inclusion measures that guarantee the realization of fundamental human rights. With the current Network Society, new information and communication technologies have emerged that have enabled greater interaction among people, considering their global reach, which has provided a greater democratization of access to information to digitally included citizens. This has led to legislation aimed at regulating and guiding online portals in terms of accessibility standards to make navigation accessible to all. Given the need for digital inclusion and Brazilian legislation regarding the rights of people with visual impairment, we ask: to what extent are the portals of the State Courts of Justice of the Brazilian Judiciary guarantee the digital accessibility of these citizens? Considering the area of concentration of the Postgraduate Course in Law of the Federal University of Santa Maria (UFSM), which are the Emerging Rights in the Global Society and the chosen line of research: Rights in the Network Society, the present research had as general objective to verify the adequacy of the portals of the Brazilian State Courts of Justice to the standards of digital accessibility established by the Accessibility Model and eMAG. For the accomplishment of the present work, the "method" of hypotheticaldeductive approach will be applied, together with the "method" of monographic procedure and the chosen research techniques were the documentary, bibliographical and the direct, systematic and non-participatory observation. It was verified that the promulgation of the Statute of the Person with Disabilities and changes in Brazilian legislation led to significant advances, but the results of direct, systematic and nonparticipative observation demonstrate a low compliance with these standards, even the standardized elements of accessibility, by virtue of the law, should be implemented in all electronic government portals in the country, evidencing a disregard for the application of digital accessibility standards in the portals of the State Courts of Brazilian Common Justice, precisely of the Judiciary, which should promote respect for legislation.